(untitled) (Revista Rupturas, 2025)
The text, based on ongoing research, aims to discuss recent experiences of cash transfer programs using social currencies in cities across the State of Rio de Janeiro. Monetary transfers through social currencies, created to mitigate the effects of the COVID-19 pandemic while managing local policies, reflect the values and institutional dynamics shaped by local politics—often marked by conservatism—and the contradictions inherent in Brazil’s own experience with cash transfers. These programs have been implemented as a substitute for broader and more structural rights, creating tensions with the basic income perspective in a context of significant setbacks in rights and material living conditions.